Differences in Eel (Monopeterus albus) Catch Results Using Fishing Gear Traps with Different Baits in Lopak Alai Village, Kumpeh Ulu District - Alfebrianti, Dhea; H, Afriani; Magwa, Rizky Janatul; Pramunsintho, Bagus; Arfiana, Bs Monica; Bareta, Ainun Rohmawati (Journal of Fish Health, 2025)
Eel (Monopterus albus) is one of the freshwater fishery products that has high economic value which is widely caught in Lopak Alai Village, Kumpe Ulu District using bubu fishing gear. This study aims to determine the differences in eel catches using bubu fishing gear with different baits in Lopak Alai Village, Kumpe Ulu District. This research was conducted in Lopak Alai Village, Kumpeh Ulu District on January 12th - February 07th, 2025. The research method used was the experimental method. The total of bubu used in this study was 60 bubu with each placement of 5 meters, the size of the bubu used was 100 cm which consisted of 2 treatments, namely using earthworm bait and golden snail bait weighing 10 grams, each bait was placed into 30 bubu with 20 repetitions. The results of the study showed that the total of eel catches (Monopterus albus) with earthworm bait was 123 with an average weight of 611 g and an average length of 45 cm, while with golden snail bait it was 204 with an average weight of 1,393 g and an average length of 49 cm. The results of the t-test analysis showed that there were differences in the catches of eels with earthworm and golden snail bait.